2009
DOI: 10.1111/j.1751-7176.2009.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypertension in the Inpatient Setting: Use of Intravenous Labetalol and Hydralazine

Abstract: J Clin Hypertens (Greenwich). 2010;12:29–33. ©2009 Wiley Periodicals, Inc. Acute blood pressure elevations are commonly treated in hospitalized patients. There are no guidelines for appropriate practice and no evidence that such treatment is useful. The authors performed a retrospective review of medical and pharmacy records to determine how often intravenous hydralazine and labetalol are ordered and administered. During a 1‐year study period, a total of 29,545 hospitalizations were recorded. The authors ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 16 publications
(26 reference statements)
4
62
0
Order By: Relevance
“…Using these prevalence figures, during a 1-year period (October 1, 2007, to September 30, 2008) in which there were 29 545 adult admissions to UMHS, some 11 100 patients were probably hypertensive. 7 Even this estimate is lower than that suggested by the results of a survey of UMHS full-time hospitalists (nϭ31), in which the modal estimate of the prevalence of established hypertension was 50% (Figure 1, left panel). In addition, patients without previously diagnosed hypertension will be encountered ( Figure 1, right panel), and even normotensive patients may experience situations (eg, anxiety or pain) that provoke transient hypertension.…”
Section: How Common Is Acute Hypertension In Hospitalized Patients?mentioning
confidence: 63%
See 2 more Smart Citations
“…Using these prevalence figures, during a 1-year period (October 1, 2007, to September 30, 2008) in which there were 29 545 adult admissions to UMHS, some 11 100 patients were probably hypertensive. 7 Even this estimate is lower than that suggested by the results of a survey of UMHS full-time hospitalists (nϭ31), in which the modal estimate of the prevalence of established hypertension was 50% (Figure 1, left panel). In addition, patients without previously diagnosed hypertension will be encountered ( Figure 1, right panel), and even normotensive patients may experience situations (eg, anxiety or pain) that provoke transient hypertension.…”
Section: How Common Is Acute Hypertension In Hospitalized Patients?mentioning
confidence: 63%
“…Dr Erickson and I previously examined the use of 2 agents frequently used at UMHS for treatment of acute hypertension (and probably for little else): intravenous labetalol and hydralazine. 7 These drugs are usually effective in lowering BP, but because there is no proven benefit of treatment, the potential exists for an adverse risk-benefit ratio.…”
Section: Physician Responses To High Bp In Hospitalized Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that most patients in hypertensive crises are treated inappropriately. 4,5 Only 15% of patients in the Studying the Treatment of Acute Hypertension registry received a continuous IV infusion of antihypertensive as first-line treatment. 6 In hypertensive urgencies, gradual lowering of BP over a 24-to 48-hour period using oral medications is the recommended approach.…”
Section: Discussionmentioning
confidence: 99%
“…It is often used as an antihypertensive on a PRN basis in the inpatient setting even for asymptomatic elevation of blood pressures [36]. It has an initial latent period of 5-15 minutes followed by a precipitous fall in blood pressure, with effects lasting up to 10 hours [37,38]. It is not recommended for use in hypertensive crisis because of its unpredictable antihypertensive effect and difficulty in titration [39].…”
Section: Fenoldopammentioning
confidence: 99%